SURVEY KE,illAAN GIZI DAN TINGKAT KESEGARAN JASMANI SISWA SEKOLAH DASAR DI DAERAH ISTIMEWA YOGYAKARTA - Suharjana Suharjana (LPMPP Universitas Negeri Yogyakarta, 2003)
This article is based on a research whose objective was toinvestigate the nutritional state and physical fitnessof elementaryschool children. For that a survey employing tests and measurementson a sampleof over 500 children obtained through quota randomsampling from a populationoffourth, fifth, and sixth graders at stateelementary schools' in the Yogyakarta Special Province wasconducted. Their nutritional state was establishedby means of theDavenport-Koup formula (Hasnan Said, 1979)and measurementstandardby Sarjono (I 992) while their physical fitness wasdeterminedby means of theTKJI (Tes Kesegaran Jasmani Indonesiaor Indonesian Physical Fitness Test)of 1999. The data wereanalyzed descriptively using percentages.The resultsshow that 2670r 51.4 % ofthese children are in theirnutritional state categorized good, with51 or 10.2 % of this groupcategorized fat and the remaining 2I6 or 41.2 % categorized normal,while 294 or 48.6% of the sample group are categorized sufferingmalnutrition, with 47 or 9.4% of them categorized very fat (oroverweight),184 or 36.8 % of them categorized thin, and 12 or 2.4% of them categorized very thin (or. nutritionally deficit orundernourished). Meanwhile, mostof the children in the sample, 312or 62.4% ofthem, are categorized bad in physical fitness, with 278